Integrasi Sains dan Nilai Islami dalam Mengenal Sumber Energi di SD Islam Nusantara Pekalongan - Rizki Diana (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the application of integration between science learning and Islamic values in introducing energy sources to students at SD Islam Nusantara Pekalongan. The focus of the research is to see how basic science concepts related to energy, such as renewable and non-renewable energy, are taught with an approach that links Islamic religious values. This research used a qualitative method with a case study design conducted at SD Islam Nusantara Pekalongan. Data collection techniques consisted of direct observation of the learning process in the classroom, interviews with teachers, and analysis of curriculum documents used in the school. The results showed that the integration of science and Islamic values at SD Islam Nusantara Pekalongan succeeded in creating a holistic learning experience for students. In the learning process, students not only understand scientific concepts about energy sources, but are also taught to see the importance of preserving nature in accordance with Islamic teachings. This lesson involves discussions on trust, environmental responsibility and sustainability in energy use. The teacher also links scientific knowledge with relevant Qur'anic verses, such as about the benefits of the sun and water as resources given by God for the good of mankind. The implication of this study shows that this integration can improve students' understanding not only in the knowledge aspect, but also in shaping characters who care about nature. The academic contribution of this research is to provide insight into the importance of an educational approach that combines science and religion, as well as providing examples of implementation that can be adopted by other Islamic schools in Indonesia to enrich students' learning experiences and form a generation that is wise in managing natural resources.